2008
DOI: 10.1002/acp.1489
|View full text |Cite
|
Sign up to set email alerts
|

Use of a structured investigative protocol enhances the quality of investigative interviews with alleged victims of child sexual abuse in Britain

Abstract: One hundred alleged victims of child sexual abuse (aged 4-13; M ¼ 9.3 years) were interviewed by police investigators about their alleged experiences. Half of the children were interviewed using the National Institute of Child Health and Human Development (NICHD) structured interview Protocol, whereas the other children, matched with respect to their age, relationship with the alleged perpetrator, and seriousness of the alleged offenses, were interviewed by investigators following the Memorandum of Good Practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
117
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(134 citation statements)
references
References 54 publications
(48 reference statements)
12
117
0
1
Order By: Relevance
“…However, the present study indicates that if general standards of interviewing improve, there is no reason to believe that repeat interviews should not also do so and continue to be of investigative value. *The difference in percentage between interviews one and two is significant at p < .05 Table 2 Mean percentages of question types used in the present study's interviews one and two and those of Lamb et al (2009) and La Rooy et al (2013) a Some of the transcripts from these samples were included in the current sample.…”
Section: Discussionmentioning
confidence: 99%
“…However, the present study indicates that if general standards of interviewing improve, there is no reason to believe that repeat interviews should not also do so and continue to be of investigative value. *The difference in percentage between interviews one and two is significant at p < .05 Table 2 Mean percentages of question types used in the present study's interviews one and two and those of Lamb et al (2009) and La Rooy et al (2013) a Some of the transcripts from these samples were included in the current sample.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of interviewing practice in various parts of the United States, United Kingdom, Canada, Sweden, Scotland, Finland, Norway, and Israel consistently show that forensic interviewers use openended prompts quite rarely (e.g. Cederborg, La Rooy & Lamb, 2008;Korkman, Santtila, & Sandnabba, 2006;Lamb et al, 1996;Lamb et al, 2009;La Rooy, Lamb & Memon, 2011; What is alarming from a service perspective is that, in many studies, considerable expense and effort was directed to training interviewers, the interviewers seem to be well-aware of the recommended practices, and often believed that they were adhering to those recommendations. Research has thus revealed a disturbing dichotomy between 'knowledge about desirable practices' and 'the actual behavior of forensic investigators' (Lamb, Hershkowitz, Orbach, & Esplin, 2008).…”
Section: Forensic Interviewing Researchmentioning
confidence: 99%
“…Studies of interviewing practice in various parts of the United States, United Kingdom, Canada, Sweden, Scotland, Finland, Norway, and Israel consistently show that forensic interviewers use openended prompts quite rarely (e.g. Cederborg, La Rooy & Lamb, 2008;Korkman, Santtila, & Sandnabba, 2006;Lamb et al, 1996;Lamb et al, 2009;La Rooy, Lamb & Memon, 2011; Myklebust & Bjorklund, 2006; Sternberg, Lamb, Davies, & Westcott, 2001). …”
mentioning
confidence: 99%
“…Bull, 2010;Davies, et al, 2000;Lamb, et al,1998;Lamb, et al, 2009;Myklebust & Bjørklund, 2006;2009;Oxburgh, Ost & Cherryman, 2010a;Oxburgh, Myklebust & Grant, 2010b;Poole & Lamb 1998). Such best practice is also promoted through investigative interviewing institutes such as the National Institute of Child Health and Human Development (NICHD; Lamb et al, 2000b).…”
Section: Questioning Stylesmentioning
confidence: 99%